Pengaruh Kepemimpinan Terhadap Kinerja Dosen dan Karyawan STIKES NU Tuban - Sugiyono Sugiyono (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
To achieve a high level of performance, of course depends on various factors that influence it. There are at least six external factors that determine the level of performance of an employee, namely: (a) environment, (b) management behavior, (c) job design, (d) education level, (e) training, (f) motivation and (g) administration payment. The purpose of this study was to analyze the effect of leadership on the performance of Stikes NU lecturers and staff in Tuban. The research method is descriptive research, the population of all lecturers and staff of STIKES NU Tuban is 120 people, the sample is divided into 3 groups (group 1 (17 people), group 2 (27 people), and group 3 (76 people)). Techniques for collecting data through observation and interviews. Data analysis uses Pearson Product moment (PPM). Based on the results of the study indicate that leadership has a significant effect on the performance of lecturers and employees in a positive direction. In addition to supporting the second hypothesis which states that leadership has a significant effect on the performance of lecturers and employees. Leadership applied by STIKES NU Tuban has been felt in accordance with the expectations and desires of lecturers and employees in the long term and caused lecturers and employees to be loyal to STIKES NU Tuban